Features of Ultrasound Examination of Gynecological Diseases - Gulomova Rano Islomjonovna (Central Asian Journal of Medical and Natural Science, 2022)
Ultrasound examination method is currently one of the leading in the diagnosis of diseases of the female genital area, because it is highly informative and has no contraindications. Regular examinations by a gynecologist, as well as ultrasound of the pelvic organs, will help to recognize the problem in time if it occurs and take appropriate measures to eliminate it.